PRODUCTION FACTORS OF AN ARTISANAL FISHERY ON A MANMADE LAKE IN COTE D’IVOIRE - Rose Danielle, Aboua Benié; Brahiman, Kien Kouassi; Armand, Agbassi; Essetchi Paul, Kouamélan (International Journal of Engineering Technologies and Management Research, 2017)
Fisheries management involves, among other things, knowledge of the actors and the catching gear used. These data are generally absent in the fisheries of Côte d’Ivoire. However, there is a strong fishing activity. To lead this study, surveys were conducted among fishermen and fishery administrators. The study of fishing activity in the area of Dioulabougou (Côte d’Ivoire, West Africa) in the district of Bouaflé done from November 2013 to February 2014 identified 88 fishermen. This population is composed of ivorians (39.77%) and foreigners (60.23%). The fishing activity is led by malians (Bambara ethnic group): 34.1%. Baoulé ethnic group (29.54% of ivorian fishermen) is the greatest ethnic group of ivorians. Two categories of fishermen stand in the fishing activity. We registered professional fishermen whose job is only fishing (84.1%) and professionals with another activity (4.5%). The fishing activity in Dioulabougou is dominated by adult aged more than 45 years (48%). Fishermen are predominantly illiterate at 42.04%. The fishing techniques used at Dioulabougou are conical fishing baskets (mesh and trunk of ronier), bamboo-traps, gillnets, bottom lines and shore seines. The illiterate situation of fishermen isa serious matter for sustainable management on fish’s resources.